ANALYSIS BREAK-EVEN POINT OF TOFU AGROINDUSTRY - Putra, Ade Fikri Maulana; Noor, Trisna Insan; Isyanto, Agus Yuniawan (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2023)
The tofu agroindustry Sumber Rezeki is one of the tofu industries that is still active in Balokang Village, Banjar District, Banjar City which has been established since 1999 until now, but until now the craftsmen do not know clearly about financial management, profits and business success. Research purposes  is to find out: (1) the cost and income of tofu agroindustry; (2) the amount of R/C; and (3) the amount of the break-even point of revenue, the break-even point of production volumes and the break-even point of prices in one production process. The type of research used is a qualitative method. The results showed: (1) The production cost of the tofu agroindustry "Sumber Sustenance" which was issued in one production process was Rp. 4,135,312.27, the production produced was 65 buckets of tofu or 18,785 pieces of tofu with a price of one bucket Rp. 90,000. The income obtained by the craftsmen is Rp. 5,950,000 and the amount of income earned is Rp. 1,814,687.73 in one production process. (2) The R/C value is 1.43, which means that for every one rupiah spent, an income of 1.43 will be obtained. So that the income of tofu agroindustry Sumber Sustenance is Rp. 0.43; (3) The break-even point of the tofu agroindustry “Sumber Rezeki” is reached at a sales value of Rp. 595,744.3 and a minimum production volume of 6.61 buckets or 1,910 pieces of Tofu with a minimum price of Rp. 63,620.19.